Nivel de aplicación del proceso de admisión y alta por el personal de enfermería a los usuarios de los servicios de pediatría y emergencia del Hospital General Puyo. Año 2013 – 2014 - Álvarez Muñoz, Gabriela Elizabeth (2015)
Keeping in mind that triage is the acceptance of the patient into care and that the release of the patient is the abandonment there of to either their domicile, a long-term care facility, or higher intensive care, there arises the desire to find a resolution to the dissatisfaction of many patients with the uncertainty involved in the admissions and release processes imparted by the pediatrics and emergency services departments of Puyo General Hospital. To this end, twenty-five nurses were chosen from the aforementioned departments for an investigative research study. The design was fixes, transversal, descriptive, bibliographic, and on campus. The techniques used were the aforementioned and direct observation of the twenty-five sampled nurses. The investigation resulted in the determination that the admission and release procedures were not being followed. The primary reasons reported for inefficiency were work overload, (reported by 68% of participants) and lack of standardized operating procedures dictating in what order to attend to patients in (reported by 100% of participants). Following this, educational discourses were help in order to develop and implement a set of admissions and release protocols to serve as a guide when providing the aforementioned services. Keywords: Admission and Release, Nursing Personnel, Pediatrics, and Emergency